Long-term safety of the tafenoquine antimalarial chemoprophylaxis regimen: A 12-month, randomized, double-blind, placebo-controlled trial. Issue 45 (January 2022) - Novitt-Moreno, Anne; Martidis, Adam; Gonzalez, Victor; Ransom, Janet; Scott, Charles B.; Dow, Geoffrey; Reid, Mark; Smith, Bryan; Zottig, Victor E.; Read, Lisa Thomas; Garver Baldwin, Lindsey S.; Chen, Fred K.
Abstract: Background: Tafenoquine is a long-acting 8-aminoquinoline approved for antimalarial prophylaxis for ≤6 months. Additional data is needed to establish the drug's longer-term safety profile, including potential ophthalmic or neuropsychiatric effects. Method: This was a randomized, double-blind, placebo-controlled trial in 600 healthy adults. Eligible subjects were randomized 1:1 to receive tafenoquine 200 mg weekly (antimalarial prophylactic regimen) or placebo for 52 weeks. Scheduled safety visits occurred at Weeks 4, 12, 24, 52 (dosing completed), and 64 (final follow-up). Safety assessments included ophthalmic changes, general and neuropsychiatric adverse events (AEs), and laboratory value changes. Results: The percentage of subjects with a protocol-defined Serious Ophthalmic Safety Event was lower in the Tafenoquine Group (18.2%) versus the Placebo Group (19%, p = 0.308). There was no significant difference between the percentages of subjects with at least one AE in the Tafenoquine Group (91.0%) versus Placebo (89.9%, p = 0.65). Common AEs seen at a significantly higher incidence for tafenoquine included reversible cornea verticillata (54.5%) and nausea (13.0%), leading to 0.0% and 0.7% discontinuations. Psychiatric AEs occurred at similar percentages in both study groups. Reversible changes in hemoglobin, methemoglobin, creatinine, and blood urea nitrogen (BUN) were noted. Conclusions: This study supports the safety of extended 52-week tafenoquine prophylaxis. Clinical trial registration Number/ClinicalTrials.gov Identifier: NCT03320174. Highlights: AE rate of tafenoquine 200 mg weekly for 52 weeks is comparable to placebo Safety of tafenoquine at ≤12 months is comparable to prior studies of ≤6 months Tafenoquine-induced changes in safety/laboratory parameters are mild and reversible Tafenoquine induces reversible cornea verticillata without retinal/vision changes Tafenoquine does not increase the risk of neuropsychiatric events vs placebo